2012
DOI: 10.1016/j.ophtha.2011.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Margin Anatomy in Patients with Glaucoma and Normal Controls with Spectral Domain Optical Coherence Tomography

Abstract: Objective To characterize optic nerve head (ONH) anatomy related to the clinical optic disc margin with spectral domain optical coherence tomography (SD-OCT). Design Cross-sectional study. Participants Open-angle glaucoma patients with focal, diffuse and sclerotic optic disc damage, and age-matched normal controls. Methods High-resolution radial SD-OCT B-scans centered on the ONH were analyzed at each clock hour. For each scan, the border tissue of Elschnig was classified for obliqueness (internally obli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
233
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(260 citation statements)
references
References 26 publications
13
233
0
9
Order By: Relevance
“…The region without the Bruch's membrane (and correspondingly, without retinal pigment epithelium and choriocapillaris) has been called parapapillary gamma zone. 20,22,23 This gamma zone was significantly correlated with high axial myopia, with the prevalence of gamma zone steeply increasing at a cutoff value of B26.0 mm of axial length (in histologically fixed globes). Interestingly, parapapillary gamma zone was not related with the presence of glaucomatous optic nerve damage.…”
Section: Optic Nerve Headmentioning
confidence: 92%
See 2 more Smart Citations
“…The region without the Bruch's membrane (and correspondingly, without retinal pigment epithelium and choriocapillaris) has been called parapapillary gamma zone. 20,22,23 This gamma zone was significantly correlated with high axial myopia, with the prevalence of gamma zone steeply increasing at a cutoff value of B26.0 mm of axial length (in histologically fixed globes). Interestingly, parapapillary gamma zone was not related with the presence of glaucomatous optic nerve damage.…”
Section: Optic Nerve Headmentioning
confidence: 92%
“…As the presence of the Bruch's membrane is essential for the presence of retinal pigment epithelium cells and choriocapillaris, the secondary macular defects in the Bruch's membrane were associated with a complete loss of retinal pigment epithelium cells and choriocapillaris, and an almost complete loss of the large choroidal vessel layer and photoreceptors. 20 These macular Bruch's membrane defects can histologically be differentiated from myopic chorioretinal atrophic areas in the macular region with a complete loss of retinal pigment epithelium cells and choriocapillaris, but with the Bruch's membrane present, similar to the histology of geographic atrophy in the framework of age-related macular degeneration.…”
Section: Choroid/bruch's Membranementioning
confidence: 96%
See 1 more Smart Citation
“…[23][24][25] The disc margin is anatomically complex and studies have shown that the clinically identified disc margin is often based on more than one tissue structure. [26][27][28] It has been demonstrated that this variability can lead to a clinical disc margin assessment that may over-and/or underestimate the amount of remaining rim in any given optic disc region. 27,29 SDOCT technology allows crosssectional visualization of the neural canal opening, which provides a distinct advantage in identifying disc margins compared to traditional stereoscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Its anatomy determines what structure is perceived clinically as the edge of the optic disc. According to their research, Reis, et al 8 found that the clinically visible disc margin corresponds to border tissue of Elschnig or both Bruch's membrane with underlying border tissue. Less frequently, it corresponds to termination of Bruch's membrane.…”
mentioning
confidence: 99%